Predictive modelling of the distribution of Clematis sect. Fruticella s. str. under climate change reveals a range expansion during the Last Glacial Maximum - Li,Mingyu; He,Jian; Zhao,Zhe; Lyu,Rudan; Yao,Min; Cheng,Jin; Xie,Lei (PeerJ, 2020)
Background The knowledge of distributional dynamics of living organisms is a prerequisite for protecting biodiversity and for the sustainable use of biotic resources. Clematis sect. Fruticella s. str. is a small group of shrubby, yellow-flowered species distributed mainly in arid and semi-arid areas of China. Plants in this section are both horticulturally and ecologically important. Methods Using past, present, and future environmental variables and data with Maximum Entropy (Maxent) modeling, we evaluated the importance of the environmental variables on the section’s estimated distributions, thus simulating its distributional dynamics over time. The contractions and expansions of suitable habitat between the past and future scenarios and the present were then compared. Results and Discussion The models revealed that the areas with high and moderate suitability currently encompass about 725,110 km2. The distribution centroid location varies between points in Ningxia and Inner Mongolia during the different scenarios. Elevation, Mean UV-B of Lowest Month, Precipitation of Coldest Quarter, and Mean Temperature of Driest Quarter were major factors determining the section’s distribution. Our modeling indicated that Clematis sect. Fruticella underwent a significant range contraction during the last interglacial period, and then expanded during the last glacial maximum (LGM) to amounts like those of the present. Cold, dry, and relatively stable climate, as well as steppe or desert steppe environments may have facilitated range expansion of this cold-adapted, drought-resistant plant taxon during the LGM. Predicted future scenarios show little change in the amounts of suitable habitat for Clematis sect. Fruticella. This study aids understanding of the distributional dynamics of Clematis sect. Fruticella, and the results will help the conservation and sustainable use of these important woody plants in Chinese arid and semiarid areas.
Keywords: Bioclimatic; Chinese Loess Plateau; Climate change; Clematis sect. Fruticella s. str.; Last Interglacial; Last Glacial Maximum; Maxent modeling; Ranunculaceae; Arid; Potential distribution